Cover Feature: Ferroelectric Fractional‐Order Capacitors (ChemElectroChem 11/2017). Issue 11 (24th October 2017) - Agambayev, Agamyrat; Patole, Shashikant P.; Farhat, Mohamed; Elwakil, Ahmed; Bagci, Hakan; Salama, Khaled N.
Abstract : The Cover Feature demonstrates fractional‐order capacitors: capacitance with no phase limitation; from theoretical modeling devices to real world products. More information can be found in the Article by A. Agambayev et al. onpage 2807 in Issue 11, 2017